2023
DOI: 10.3847/1538-4357/acd04d
|View full text |Cite
|
Sign up to set email alerts
|

Shedding New Light on Weak Emission-line Quasars in the C iv–Hβ Parameter Space

Abstract: Weak emission-line quasars (WLQs) are a subset of type 1 quasars that exhibit extremely weak Lyα + N v λ1240 and/or C iv λ1549 emission lines. We investigate the relationship between emission-line properties and accretion rate for a sample of 230 “ordinary” type 1 quasars and 18 WLQs at z < 0.5 and 1.5 < z < 3.5 that have rest-frame ultraviolet and optical spectral measurements. We apply a correction to the Hβ-based black hole mass (M BH) estimates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Based on the continuum fitting method, Marculewicz & Nikolajuk (2020) found that most of the WLQs have a BH mass larger than 10 9 M e and pointed out that the BH mass estimated from FWHM(Hβ) is underestimated. However, Ha et al (2023) proposed that the BH mass estimated from the traditional method of the broad-emission-line region sizeluminosity relation may be overestimated by up to an order of magnitude, where the corrections based on the strength of the optical Fe II emission and possible blueshift of C IV lines are applied. It should be noted that the larger value of R Fe II = Fe II (4434-4684 Å)/Hβ in WLQs may not be an indicator of high Eddington ratios, as found in narrow-line Seyferts, but caused by the weaker Hβ emission, since both low-ionization and high-ionization lines can become weaker in WLQs (see Figure 3 and Shemmer et al 2010).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Based on the continuum fitting method, Marculewicz & Nikolajuk (2020) found that most of the WLQs have a BH mass larger than 10 9 M e and pointed out that the BH mass estimated from FWHM(Hβ) is underestimated. However, Ha et al (2023) proposed that the BH mass estimated from the traditional method of the broad-emission-line region sizeluminosity relation may be overestimated by up to an order of magnitude, where the corrections based on the strength of the optical Fe II emission and possible blueshift of C IV lines are applied. It should be noted that the larger value of R Fe II = Fe II (4434-4684 Å)/Hβ in WLQs may not be an indicator of high Eddington ratios, as found in narrow-line Seyferts, but caused by the weaker Hβ emission, since both low-ionization and high-ionization lines can become weaker in WLQs (see Figure 3 and Shemmer et al 2010).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…A primary interest going forward would be bolstering the sample with supplementary observations of quasars, primarily at z ∼ 3, in order to obtain statistically meaningful results on a potential redshift dependence, and further improve UV-based redshift determinations. It will also be interesting to test our prescriptions at the highest accessible redshifts, where considerably larger C IV blueshifts have been observed in sources at z  6, perhaps due to higher accretion rates (e.g., Meyer et al 2019;Schindler et al 2020;Ha et al 2023). Another avenue of further investigation includes increasing the sample size of quasars with significantly higher spectral resolution, e.g., using Gemini's Spectrograph and Camera for Observations of Rapid Phenomena in the Infrared and Optical (Robberto et al 2020), in order to further improve the UV-based redshift corrections by obtaining more accurate line peaks of spectral features.…”
Section: Discussionmentioning
confidence: 99%